(untitled) (Texas Journal of Engineering and Technology, 2024)
Recruitment of employees to internal affairs agencies is important in ensuring law and order and public safety. The effectiveness of internal affairs agencies directly depends on the professional skills, personal qualities and moral stability of employees. The article examines the main aspects of recruitment of personnel to internal affairs agencies, including legislative requirements, selection stages, methods of candidate assessment, as well as difficulties that arise in the recruitment process. Particular attention is paid to psychological tests that check the level of physical fitness and develop the motivation of candidates